IEEE PES Power Systems Conference and Exposition, 2004.
DOI: 10.1109/psce.2004.1397498
|View full text |Cite
|
Sign up to set email alerts
|

A new fuzzy logic power system stabilizer performances

Abstract: This paper describes the performances of a new power system stabilizer, the Fuzzy Logic PSS (FLPSS). It is basically a PID (proportional-integral-derivative) type FLPSS with adjustable gains added outside in order to keep a simple structure. The FLPSS uses the generator speed deviation as primary input from which the accelerating power is derived as a secondary input. In order to validate the FLPSS, it has been compared with two reference stabilizers, the IEEE PSS4B and IEEE PSS2B from the IEEE Std 421.5. Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Kundur Test system with four machines-two areas [20] (presented in Fig. 6) is widely used in the Dynamic stability assessment [8,13,21]. The system has Symmetrical two areas with two machines in each area connected by weak tie-lines.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Kundur Test system with four machines-two areas [20] (presented in Fig. 6) is widely used in the Dynamic stability assessment [8,13,21]. The system has Symmetrical two areas with two machines in each area connected by weak tie-lines.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…It can be observed that the spectrum of the power deviation signal exhibits a dominant oscillating mode around 1.2 Hz, which corresponds to the poorly damped electromechanical local mode of the synchronous 10 kVA generator against the large power system. By using the collected input-output data, a fourth order ARX model, having the structure presented in (11), was estimated. The values for the estimated parameters are provided in Table 2.…”
Section: Description Of the 10 Kva Study Power Systemmentioning
confidence: 99%
“…The adaptive methodologies investigated include: self-tuning control [7], robust-optimal control [8][9][10], fuzzy [11] and fuzzy-neural techniques [12], among others. In [11], a fuzzy logic PSS (FLPSS) was designed and its performance was assessed, by simulation studies, in a four-machine test system. The authors show that the performance obtained by using the FLPSS was comparable with the obtained when applying PSS2B or PSS4B controllers.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainity cannot be determined with its exact value, because of its complexity and rather type-1 fuzzy sets gives much senser than using crisp sets [21]. So, it is difficult to measure an uncertain membership function .…”
Section: Type 2 (T2) Fuzzy Logic Controllersmentioning
confidence: 99%